Potential targets for controlling Bactrocera dorsalis using cuticle‐ and hormone‐related genes revealed by a developmental transcriptome analysis. Issue 6 (14th February 2020) - Liu, Shi‐Huo; Xia, Ying‐Dan; Zhang, Qiang; Li, Wei; Li, Run‐Yan; Liu, Yi; Chen, Er‐Hu; Dou, Wei; Stelinski, Lukasz L; Wang, Jin‐Jun
Abstract: BACKGROUND: The oriental fruit fly, Bactrocera dorsalis (Hendel), is an important agricultural pest and has developed resistance to many insecticides. To investigate vital genes participating in metamorphosis for development of additional control strategies, a comprehensive transcriptome analysis covering ten developmental stages of B. dorsalis was performed. RESULTS: There were 2132, 952, 1062, 2301 and 1333 differentially expressed genes identified during hatching, 1st‐instar larval molting, 2nd‐instar larval molting, pupariation and emergence, respectively. Further expression analyses indicated that genes in hormone‐ (20‐hydroxyecdysone and juvenile hormone) and cuticle‐ (chitin and cuticle protein) related pathways were essential for metamorphosis in B. dorsalis . Among chitinase ( Cht ) genes, BdCht‐5, −8 and −10 were differentially expressed during larval–larval, larval–pupal and pupal–adult moltings. However, BdCht7 was differentially expressed during egg–larval and larval–larval moltings. Knockdown of BdCht7 at the 1st‐instar larval stage disrupted normal development of larvae and was lethal to B. dorsalis . Among cuticle protein (CP) genes, 15 genes ( BdCPLCG‐1, BdCPLCP‐2, BdCPAP1‐B2, BdRR1‐21, BdRR1‐31, BdRR2‐15, BdRR2‐26, BdRR2‐30, BdRR2‐32, BdTweedle‐9, BdTweedle‐24, BdRR2‐10, BdCPAP3‐C1, BdRR1‐34 and BdRR1‐41 ) were differentially expressed during four of five types of moltings. Among hormone‐relative genes, BdJHBP‐4, −9 and −13 were differentially expressed during all five types of moltings, whereas BdJHBP‐5, −12 and BdHR4 were differentially expressed during four of five types of moltings. CONCLUSION: This study reveals critical genes involved in development and metamorphosis of B. dorsaslis, and BdCht7 is dispensable for larval survival. It also provides comprehensive transcriptome information for finding more molecular targets to control this pest. © 2020 Society of Chemical Industry Abstract : A comprehensive transcriptome analysis covering ten developmental stages of Bactrocera dorsalis revealed potential targets for fruit fly control, and provided a substantial amount of gene pool information. © 2020 Society of Chemical Industry